The complete plastid genome sequence of Gleditsia sinensis, an ancient medicinal tree in China. Issue 3 (2nd July 2020) - Bai, Ji-Qing; Yang, Lei; Gao, Su; Zhu, Wei-Feng; Huang, Lu-Qi
Abstract: Gleditsia sinensis Lam. (Leguminosae) is an ancient medicinal tree in China. In this study, we first characterized the whole plastid genome sequence using the illumination sequencing technology. The length of the plastid genome was 163, 151 bp, including the large single copy (LSC) region of 91, 515 bp, the small single copy (SSC) region of 19, 250 bp, and two reversed duplicate regions (IR) of each 26, 193 bp. The genome of G. sinensis contains 130 genes, including 85 protein-coding genes, 37 transfer RNA (tRNA) and 8 ribosomal RNA (rRNA). Phylogenetic analysis showed that G . sinensis was placed as a sister to the congeneric G . japonica .